2019
DOI: 10.18805/ijare.a-5074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of foliar spray and fertilizer levels on growth and yield of vegetable cowpea [Vigna unguiculata (L.) Walp.]

Abstract: Field experiments were conducted to study the effect of foliar spray and fertilizer levels on growth and yield of vegetable cowpea (PKM 1) during kharif season of the years 2015 and 2016 at Western block, Horticultural College and Research Institute, Periyakulam. Results revealed that in general vegetable cowpea responded well to the increased dose of fertilizers along with foliar spraying of 2 % DAP and pulse wonder during flowering and pod formation stages. Application of 125 % RDF along with 2 % DAP spray a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…There was an increase of 24.4% (with 2% WSF) and 23.16% (with 1.5% WSF) in grain yield over control (Mudalagiriyappa et al, 2016). Application of 125% RDF along with 2% DAP spray at flowering and pod formation stages recorded significantly higher growth attributes resulted in increased pod yield of cowpea as compared to 100% RDF (Kavitha et al, 2019). Therefore, foliar nutrition is being recognized as an important method of fertilization in modern agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…There was an increase of 24.4% (with 2% WSF) and 23.16% (with 1.5% WSF) in grain yield over control (Mudalagiriyappa et al, 2016). Application of 125% RDF along with 2% DAP spray at flowering and pod formation stages recorded significantly higher growth attributes resulted in increased pod yield of cowpea as compared to 100% RDF (Kavitha et al, 2019). Therefore, foliar nutrition is being recognized as an important method of fertilization in modern agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…The higher haulm yield may be due to the beneficial effect of nitrogen on morpho-physiological characters, which influenced growth attributes such as plant height and number of branches/plant. Das and Jana (2015) [5] in pulses and Kavitha et al (2019) [9] in cowpea also found that significantly higher yield attribute like pod length, pods/plant and seeds/pod. The results are in line with findings of Choudhary and Yadav (2011) [3] , Singhal et al (2015) [18] and Dey et al (2017) [6] in cowpea.…”
Section: Impact Of Pgrs Organic and Inorganic Source Of Foliar Nutrie...mentioning
confidence: 94%
“…The highest number of fruits per vine and fruit weight were recorded in foliar application of DAP (1.5%) and boric acid (0.1%) at 35 DAS followed by one more spray of boric Foliar Nutrition with Water Soluble Macro and Micro Nutrient Fertilizers for Yield Maximization in Bush Vegetable Cowpea acid (0.1%) at 45 DAS in cucumber (Mondal et al, 2017). An enhancement in number of flowers per plant, number of pods per plant, pod length and pod weight were noticed in cowpea due to application of 125 per cent RDF along with 2 per cent DAP spray at flowering and pod formation stages (Kavitha et al, 2019). Foliar nutrition of Zn (100 mg L -1 ) and B (100 mg L -1 ) recorded significantly higher fruit length and number of fruits per plant in tomato receiving (Saravaiya et al, 2014).…”
Section: Introductionmentioning
confidence: 94%